Freeze-Drying of Streptomyces aureofaciens Endospore Culture - Ananyina, A. Ye.; Tsutsayeva, A. A.; Balyberdina, L. M.; Grisha, I. G.; Shcheglov, A. V. (Problems of Cryobiology and Cryomedicine, 2013)
The stages of technological process of lyophilization of spore cultures, Streptomyces aurefaciens on agar plates providing a high integrity of lyophilized microbe cells both after freeze-drying and after their following storage under hypothermia conditions for 4 years have been developed.